Facile synthesis of isomeric fullerene derivatives as acceptors for high performance organic photovoltaic. Issue 42 (21st October 2015) - Lin, Guoming; Cui, Rongli; Huang, Huan; Guo, Xihong; Yang, Shangyuan; Li, Cheng; Dong, Jinquan; Sun, Baoyun
Abstract: Two new isomeric fullerene derivatives, {6}-1-(3-(Benzoyl)propyl)-{5}-1-phenyl [5, 6] C61 and 1-(3-(Benzoyl)propyl)-1-phenyl[6, 6] C60, have been synthesized efficiently through a 1, 3-dipolar cycloaddition of a tosylhydrazone to provide relatively high photovoltaic performances. A systematic study on the optical, electrochemical and photovoltaic properties of the fullerene derivatives has been performed. In particular, the polymer solar cell (PSC) based on {6}-1-(3-(Benzoyl)propyl)-{5}-1-phenyl [5, 6] C61 and poly(3-hexylthiophene) showed a power conversion efficiency of 2.81%, which is higher than that of PCBM (2.53%) under the same device conditions. Graphical abstract: